Comparison of pulse oximetry and colour: a better index of oxygenation in neonatal resuscitation - Bansal, Akanksha; Das, Ghanshyam; Ambey, Ravi (International Journal of Contemporary Pediatrics, 2016)
Background:Colour is an unreliable indicator of tissue oxygenation in the first few minutes of life. Little data is available about the progression of SpO2 in the new-borns delivered by normal vaginal route and caesarean section. So this study was conducted. The objectives of this study were to compare the new-born’s colour and oxygen saturation readings as an index of oxygenation and to find a more reliable one, and to compare the oxygen saturation profiles of the new-borns delivered by normal vaginal route and caesarean section. Methods: This was a prospective observational study conducted over a period of one year in a tertiary care hospital on 500 newborns between 28-42 weeks, requiring routine care. Simultaneous assessment of colour and oxygen saturation readings was done at 30 second intervals after birth till 10 minutes of life. Results:No significant difference has been found in the median SpO2 values of the new-borns requiring routine care that were pink and cyanosed since birth (p≥ 0.05). About 5.30 minutes required for most of the cyanosed new-borns to become pink (p≥ 0.05). Mean time±SD required for cyanosed new-born for getting pink was 1.96±1.33 minutes. Oxygen saturation rises slowly in new-borns delivered by caesarean section as compared to those delivered vaginally, especially in the first few minutes of life and more in preterm than term new-borns. Conclusions:Unnecessary use of oxygen can be avoided by taking into account pulse oximetry. Separate sets of reference SpO2 should be used for new-borns delivered by normal vaginal route and caesarean section.